2012
DOI: 10.1126/science.1219681
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Role of the Temporal-Parietal Junction in Predicting Socially Guided Decisions

Abstract: To make adaptive decisions in a social context, humans must identify relevant agents in the environment, infer their underlying strategies and motivations, and predict their upcoming actions. We used functional magnetic resonance imaging (fMRI), in conjunction with combinatorial multivariate pattern analysis (MVPA), to predict human participants’ subsequent decisions in an incentive-compatible poker game. We found that signals from the temporal-parietal junction (TPJ) provided unique information about the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
183
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(202 citation statements)
references
References 60 publications
(33 reference statements)
15
183
2
2
Order By: Relevance
“…In this case, the main difference in neural processing during social and non-social decisions may not lie in local value computations but rather in the remote neural regions that may provide the information on which these computations are based. Consistent with this view, several types of social decisions reviewed above have been associated with responses in regions outside the classic valuation circuitry (such as the dlPFC 113 , TPJ 11,114 and dmPFC 70,75 ) that may in principle provide input that is relevant for the construction of uniquely social values. This possibility has been formally tested with connectivity analyses 38,45,57,58,67,69,74,113,115 , which have revealed that different types of social decision making and learning involve functional coupling between BOLD responses in 'classic' valuation regions and BOLD responses in regions outside the reward circuitry (for example, in the TPJ or dmPFC).…”
Section: Adaptive Codingmentioning
confidence: 85%
See 1 more Smart Citation
“…In this case, the main difference in neural processing during social and non-social decisions may not lie in local value computations but rather in the remote neural regions that may provide the information on which these computations are based. Consistent with this view, several types of social decisions reviewed above have been associated with responses in regions outside the classic valuation circuitry (such as the dlPFC 113 , TPJ 11,114 and dmPFC 70,75 ) that may in principle provide input that is relevant for the construction of uniquely social values. This possibility has been formally tested with connectivity analyses 38,45,57,58,67,69,74,113,115 , which have revealed that different types of social decision making and learning involve functional coupling between BOLD responses in 'classic' valuation regions and BOLD responses in regions outside the reward circuitry (for example, in the TPJ or dmPFC).…”
Section: Adaptive Codingmentioning
confidence: 85%
“…By contrast, researchers studying social decisions have traditionally paid less attention to motivational processes, such as reward and value coding; instead, they have focused on identifying neurocognitive processes that may have uniquely evolved to guide social behaviour 7 . This emphasis on 'social-specific cognition' has identified, for example, that different visual areas seem to be functionally specialized for the perception of faces or bodies 8 and that the dorsomedial prefrontal cortex (dmPFC) and the temporoparietal junction (TPJ) may be specifically involved in representing the intentions, emotions or actions of other people [9][10][11] . The idea of 'social-specific cognition' thus implies that the control of social and non-social behaviour should fundamentally differ in terms of neural architecture and information processing demands 12 .…”
mentioning
confidence: 99%
“…To this end, we tested the predictions of two competing ideas on the role of the TPJ during prosocial choice in general, and social discounting in particular. Previous research showed that this region is involved in tasks requiring the ability to represent and understand others' perspectives (12,13) and in social and selfish decisions (14)(15)(16)(17). Thus, the TPJ's implication in prosocial choice, perspective taking, empathizing, and ToM suggests that it plays a role in…”
mentioning
confidence: 99%
“…Recent research has sketched a rough outline of the neural circuits that contribute to complex social behavior (4,5). These comprise a set of domaingeneral brain areas, including the ventromedial prefrontal cortex and ventral striatum, that process information about reward and punishment and contribute to decision-making, and a set of specialized areas, including the temporoparietal junction and medial prefrontal cortex, that process specifically social information (4,6). How social and nonsocial signals in these circuits are integrated to mediate decisions with respect to others remains imperfectly understood, in part, due to the indirect nature of hemodynamic signals measured in human neuroimaging experiments that constitute the bulk of this research.…”
mentioning
confidence: 99%